Penerapan Metode Guided Note Taking untuk Meningkatkan Keaktifan Belajar IPS Siswa Kelas IV SDN 7 Tikala Kecamatan Tikala Kabupaten Toraja Utara - Resdita Denna; Nur Abidah Idrus; Siti Raihan (Pinisi Journal Pendidikan Guru Sekolah Dasar, 2023)
The problem that occurs in class IV SDN 7 Tikala is that the teacher only provides learning material using the lecture method so that students just sit listening without understanding the lessons given by the teacher so that students feel bored and become less active during the learning process. This study aims to determine the application of the guided note talking learning method to increase the social studies learning activity of fourth grade students at SDN 7 Tikala, North Toraja Regency with reference to indicators of student activity. This research method uses a qualitative approach with the type of classroom action research. The population in this study were 26 grade IV students at SDN 7 Tikala, North Toraja Regency. Data collection techniques through observation, student learning activeness questionnaires and documentation. The results showed that there was an increase in student learning activeness from cycle I which was in the poor category, to cycle II which was in the very good category. The conclusion of this study is that there is an increase in student activity with the application of the Guided Note Taking method in class IV students at SDN 7 Tikala, North Toraja Regency.